Analysis of hospital service areas in Istanbul - Vedia Dokmeci; M. Aykut Sadi (European Regional Science Association (ERSA), 1998)
After 1950's, the rapid expansion of Istanbul has created tremendous demand for new public facilities as well as the need for evaluation of existing facilities. Although the service areas of hospital is a very important information in order to use efficently scarce resources, there are very few studies on this subject in devoloping countries. This study investigates the spatial behavior of in patients in relation to three different types of hospitals ( teaching, general public and private) in order to provide background for the efficient planning of health facilities in Istanbul. According to the results, all three types of hospitals receive patients from different parts of the city as well as throughout the country. The service areas of these hospitals are investigated also according to their location within the different zones of the city. As the speciality of the hospitals increases, the density of the patients becomes more widely distributed than the local hospitals. According to the results, the areas which are not served by any hospital are determined. Further, research is suggested on more detailed analysis of spatial behavior of patients with respect to patients' characteristics.
Keywords: 330